Release and Social Reintegration of Prisoners from the Perspective of John Rawls’ Theory of Justice - Markus Marselinus Soge (Faculty of Law, Universitas Pelita Harapan | Lippo Village, Tangerang 15811 - Indonesia, 2022)
The conditional release of corruption prisoners is contrary to the sense of justice. Penitentiary releases prisoners for adhering to the concept of social reintegration as an important stage in the correctional system in which prisoners are reunited with society. The problem to be discussed is how the perspective of John Rawls’ theory of justice on conditional release and social reintegration of prisoners. The purpose of the research is to discuss the perspective of John Rawls’ theory of justice on conditional release and social reintegration of prisoners. Normative legal research methods are used with legislation and conceptual approaches that analyse secondary data, namely primary legal materials and secondary legal materials, where data is collected using document or library study techniques, then analysed qualitatively. The conclusions, first, the release especially conditional release of prisoners including corruption prisoners is the right of prisoners after they have met the predetermined requirements and the social reintegration is an important stage in reuniting prisoners with society. Second, the perspective of John Rawls’ theory of justice on conditional release and social reintegration of prisoners prioritizes equal treatment of prisoners including corruption prisoners who have basic rights and freedoms. The distribution of income and wealth to prisoners does not need to be the same but must benefit everyone including prisoners, and there is access for prisoners to positions and responsibilities as members of society.